The influence of financial bootstrapping and digital transformation on financial performance: evidence from MSMEs in the culinary sector in Indonesia - Maria Rio Rita; Pambayun Kinasih Yekti Nastiti (Cogent Business & Management, 2024)
To reduce dependence on external funding, financial bootstrapping can be an alternative low-cost funding solution for MSMEs. Cost efficiency can also be achieved by carrying out digital transformation in business operational activities. Furthermore, cost efficiency will lead to improved financial performance of MSMEs. This research investigates the influence of financial bootstrapping and digital transformation on the financial performance of MSMEs. Data collection was carried out through a field survey involving several enumerators and 180 respondents. The respondents of this research were female MSME entrepreneurs in the culinary sector in Central Java Province, Indonesia. The data was analyzed using the Partial Least Squares-Structural Equation Modeling (PLS-SEM) method. The research results revealed that financial bootstrapping and digital transformation have a significant positive effect on the financial performance of MSMEs. Furthermore, this study offers recommendations to improve the financial performance of MSMEs. Entrepreneurs must be creative in utilizing cheap internal funding sources and willing to adopt digital technology to increase operational efficiency and customer satisfaction.Fieldsentrepreneurship and small firm management; business, management and accounting; entrepreneurial finance
Keywords: 650; financial performance; financial bootstrapping; digital transformation; female entrepreneurs; MSME